The Effectiveness of Using Wordwall as a Media for Mathematical Learning Assessment in Madrasah Ibtidaiyah - Muflikhah, Ila Khayati; Kamal, Rahmat (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
Mathematics lessons are one of the lessons that are considered difficult, so educators must be creative in choosing learning media to reduce the stereotype that mathematics lessons are difficult. One assessment medium that can be used to attract student interest is Wordwall. This research aims to determine the effectiveness and level of enthusiasm for Wordwall as an assessment medium in mathematics learning. The method used in this research is descriptive quantitative with a one-group pretest-posttest research design. The sample from this study uses a saturated sample, which means the entire population is included in the sample. The number of class V students at MI Soko, Pekalongan City is 36 students. Data collection was carried out by administering questionnaires and carrying out pretest-posttest related to mathematics questions. Then the data analysis technique uses the N-gain test, hypothesis testing, and Likert scale. The results of this research are: (1) Students feel enthusiastic about carrying out assessments using Wordwall with an enthusiasm percentage of 81.4% with effective information. (2) The use of Wordwall as a medium for assessing mathematics learning has proven to be effective with an N-gain value of 0.33, including the medium category and hypothesis testing with a large value. 0.000 < 0.05 which proves that there is a significant difference between before using Wordwall (pretest) and after using Wordwall (posttest). It is hoped that the research results will be able to provide information for educators regarding assessment media that are appropriate to developments in this century. The use of wordwalls has also been shown to be able to improve learning outcomes and student enthusiasm, especially in learning mathematics